Does the Oil Revenues Affect the Macro Economic Variables Performance in Africa ? A Panel Data Analysis - Ayoub, Zeraibi (International Journal of Economics, Business and Management Studies, 2019)
Oil revenues play a vital and central role in the economies of developing countries and African countries are among the countries whose macroeconomic variables are affected by oil revenues. The objective of this study is to analyze and investigate the role of oil revenues on the macroeconomic variables in most of the oil-producing African countries. The study employed the Econometric method Pooled Ols model and the fixed and random technique; data used was time sires cross panel data in the period (2000-2018). Based on the literature review, the selected sample study was on countries such as (Nigeria, Algeria, Angola, Gabon, Egypt, Congo, Sudan, Chad, Ghana). The Gross Domestic Product was employed as the target variable and Oil Revenues (Oiler), inflation (CPI), Exchange rate (Ex), exports (Exp), Foreign Direct Invest (FDI), money supply (M2) as independent variables. The study result and analysis of the data indicated that oil revenue has an impact on most of the macroeconomic variables except CPI and M2. A strong positive correlation between oil revenue and GDP growth rate on the countries’ samples study was also indicated. The study concluded that one of the most important macroeconomic variables is oil revenues. It also recommended that African countries need support and need to put more effort in building strong economies that are not dependent on oil revenues; also to work on diversifying the revenues of the states and work to preserve the right of the next generation to exploit natural and oil resources.